Data Rate Estimation for Wireless Core-to-Cache Communication in Multicore CPUs - Maria S. Komar; V. Petrov; K. Borunova; D. Moltchanov; E. Koucheryavy (Моделирование и анализ информационных систем, 2015)
In this paper, a principal architecture of common purpose CPU and its main components are discussed, CPUs evolution is considered and drawbacks that prevent future CPU development are mentioned. Further, solutions proposed so far are addressed and a new CPU architecture is introduced. The proposed architecture is based on wireless cache access that enables a reliable interaction between cores in multicore CPUs using terahertz band, 0.1-10THz. The presented architecture addresses the scalability problem of existing processors and may potentially allow to scale them to tens of cores. As in-depth analysis of the applicability of the suggested architecture requires accurate prediction of traffic in current and next generations of processors, we consider a set of approaches for traffic estimation in modern CPUs discussing their benefits and drawbacks. The authors identify traffic measurements by using existing software tools as the most promising approach for traffic estimation, and they use Intel Performance Counter Monitor for this purpose. Three types of CPU loads are considered including two artificial tests and background system load. For each load type the amount of data transmitted through the L2-L3 interface is reported for various input parameters including the number of active cores and their dependences on the number of cores and operational frequency.